The Role of African Traditional Religion, Culture and World-View in the Context of Post- War Healing among the Dinka Community of Southern Sudan - Kamwaria, Alex; Katola, Michael (Centre for Promoting Ideas, 2012)
This article explores how the Dinka concept of health and illness is filtered and interpreted through religion, culture and world-view. Health and illness have a broader dimension that includes the religious, cultural, and ecological components. The Dinka community has many rituals directed at ensuring good health, preventing danger to health, curing afflictions, removing impurities in people and homesteads, and protecting people, their animals and crops. Health and illness are not just physical conditions, but are also linked to the beliefs and practices of the Dinka traditional religion. They are religio-cultural matters which have to be dealt with in religio-cultural ways.
Keywords: African Traditional Religion; Rituals; World-view; Post-war healing